Collaborative Learning in Inclusive Education: Constructing Tolerant Attitudes of Students at Pondok Modern Darussalam Gontor - Maskuri Maskuri; Junaidi Mistar; Syarifah (Universitas Negeri Semarang, 2026)
Learning strategies that are focused not just on academic success but also on the development of social attitudes—particularly tolerance in the setting of a heterogeneous society—are required by inclusive education. The purpose of this study is to examine how collaborative learning in inclusive education helps students at the Pondok Modern Darussalam Gontordevelop attitudes of tolerance. This study combined a case study design with a qualitative methodology. Students, instructors, and caregivers at Islamic boarding schools participated in semi-structured interviews, participant observation, and documentation to gather data. Thematic analysis approaches were used to analyze the data. The study's findings show that regular use of collaborative learning techniques fosters an inclusive and engaging environment for social interaction in both the Islamic boarding school's formal and informal learning activities. Through processes of positive interdependence within groups, open discourse, collaborative reflection, and institutional support for the inclusion concept, students develop tolerance attitudes. Students can observe firsthand how to manage conflict, appreciate diversity, and develop empathy in the Islamic boarding school's communal life through collaborative learning. By supporting collaborative learning as an educational approach that contributes to the development of emotive and social values, this study makes a theoretical contribution. The study's practical conclusions suggest that enhancing collaborative learning is essential to creating inclusive Islamic boarding school-based instruction.